Diagnostic accuracy of interleukin-33 for tuberculous pleural effusion: A systematic review and meta-analysis. Issue 31 (6th August 2021) - Shi, Xin-Yu; Yi, Feng-Shuang; Qiao, Xin; Pei, Xue-Bin; Dong, Shu-Feng
Abstract: Background: The detection of interleukin 33 (IL-33) in pleural effusion may be more sensitive in diagnosing tuberculous pleural effusion (TPE). The present study aimed to assess the accuracy of pleural IL-33 for the diagnosis of TPE by means of meta-analysis and systematic review of relevant studies. Method: After retrieving the published studies, the sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, diagnostic odds ratio, and a summary receiver operating characteristic curve were assessed to estimate the usefulness of pleural IL-33 in diagnosing TPE using meta-analysis with a random-effects model. We also performed meta-regression and subgroup analysis. Results: A total of 639 patients from 6 studies were analyzed. The pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio were 0.87 (95% confidence interval [CI], 0.82–0.91), 0.76 (95% CI, 0.72–0.80), 6.54 (95% CI, 2.65–16.15), 0.17 (95% CI, 0.10–1.27), and 45.40 (95% CI, 12.83–160.70) respectively. The area under the curve was 0.94. The composition of the included population was the main cause of heterogeneity and subgroup analysis showed that pleural IL-33 had a higher specificity (0.93, 95% CI 0.87–0.96) when used for differential diagnosis between TPE and malignant pleural effusion. Conclusion: The detection of IL-33 alone in pleural effusion seems to not be an efficient diagnostic marker for TPE but may serve as a novel biomarker to differentiate between TPE and malignant pleural effusion.